(3HVGYI GdeLnhOs - (3eMeO Hf MSf GdSfLGQjs
(3ChdgG (B:s
(3jbhd QGLi cQe GdZaGQ eMeO Hf MSf GdSfLGQi s
(3BNQgG (B:s
(3hGdMeO ddg Ydi GdJeGe hGdTcQ ddg Ydi GdESdGe s
(3CQLhRI ai GdCbdGe hCOhGJ GdcJGHI ai GdNW hCUhdgs
(3jdjgG bUjOI GHf GdHhGH ai Yde UfGYI GdcJGHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B185 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B195 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI HGjRjO YehejI HGSJGfHhd (B(8012) s
Keywords: (3GdNW hCdGJgs